Rendimiento potencial de combustibles sólidos de tres especies del bosque varillal húmedo de Nina Rumi, Loreto-Perú, 2021 - Vásquez Godfroyd, Claudia Elena (2022)
In the present study the potential yield of solid fuels , roasted wood and charcoal of Inga sp ' shimbillo , Alchornea triplinervia " zancudo caspi " and Croton palanostigma " shamboquiro ' of the humid vagal forest in the Nina rumi area was determined . To obtain the samples an inventory of the humid rod forests was carried out and the species were selected by the abundance of the population per hectare and with allometric formulas the tree biomass was determined, the laboratory data was used to calculate the yields per hectare The results show the largest tree population is found in the " shimbillo " species , followed by " zancudo caspi " and " shamboquiro " with 32 trees / ha , 24 trees / ha and 15 trees / ha , respectively . The highest potential yield in toasted wood was in " shimbillo " with 56.37 kg / tree and 1,803.97 kg / ha , followed by " zancudo caspi " with 25.77 kg / tree and 618.41 kg / ha ; the " shamboquiro " it is the one with the lowest potential yield with 13.44 kg/tree and 618.41 kg/ha. The highest potential carbon yield has also been determined in "shimbillo" with 26.53 kg/tree and 848.94 kg/ha; followed by ' Zancudo caspi ' with 12.13 kg / tree and 291.02 kg / ha ; and in lower yield in " shamboquiro " with 6.32 kg / tree and 94.85 kg / ha The Kruskal - Wallis statistical test and Dunn 's comparison indicate that there is significance in the comparison of yield in toasted wood and " shimbillo " charcoal with " Zancudo caspi " and " Shamboquiro”